Les maisons forestières, de la Direction générale des forêts à l’ONF (xixe-xxie siècle). Les oubliées du paysage de la forêt domaniale - Stéphanie Barioz Aquilon (Projets de Paysage)
Resulting from a serial programme developed during the 19th century as part of the reorganisation of the French forestry administration, forestry lodges are a forgotten heritage in the history of the French national forests and are often isolated, modest dwellings. Yet their implantation and architectural design shed light on a policy and relationship to the forest that has evolved over time. Under what conditions and according to what typologies did this official housing for loggers and forest rangers impose itself in the French national forests in the 19th century? How and why did the model evolve from the 20th century onwards? Finally, how has the massive sale of forestry lodges in recent decades been received and what reconversions has it brought about? This article, based on an assignment carried out within the framework of a general inventory of the French cultural heritage, presents archival research cross-referenced with field observations to produce an unprecedented synthetic study.